Phonological Atlas 10 is about the language form between Shaqlawa and Koya districts - Sakar Anwar Hameed; Yousif Shareef Saeed (Zanco Journal of Humanity Sciences)
Dialectical Atlas consists of lots of language maps, which shows the spread of a language phenomenon in a specific area. This map shows the native speakers of this area through using different signs like voice, lexical, grammar and semantics.